Underestimation of Cerebral Perfusion on Flow-Sensitive Alternating Inversion Recovery Image: Semiquantitative Evaluation with Time-to-Peak Values - Kim, H.S.; Kim, S.Y.; Kim, J.M. (American Journal of Neuroradiology, 2007)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf